Spatial distribution of mixed milk feeding and its determinants among mothers of infants aged under 6 months in Ethiopia: Spatial and geographical weighted regression analysis - Mekuriaw Nibret Aweke; Muluken Chanie Agimas; Moges Tadesse Abebe; Tigabu Kidie Tesfie; Meron Asmamaw Alemayehu; Werkneh Melkie Tilahun; Gebrie Getu Alemu; Worku Necho Asferie (PLoS ONE, 2025)
Background Mixed milk feeding is defined as providing formula and/or animal milk along with breast milk to infants under six months old which is prevalent in many countries. However, this practice is generally not recommended as it can reduce the intake of breast milk, depriving the infant of its optimal nutritional and immunological benefits. Unlike formula, breast milk contains complex bioactive constituents that promote intestinal and pancreatic growth and develop mucosal defenses. The aim of this study was to analyze the spatial distribution and predictors of MMF practices in Ethiopia. Methods This study utilized data from the 2019 Mini-Ethiopian Demographic and Health Survey (MiniEDHS), a nationally representative cross-sectional survey conducted from March to June 2019. The total weighted sample size derived from the data examined in this study amounted to 524 infants. The data analysis used Global Moran’s I for spatial autocorrelation and the Getis-Ord Gi * statistic for local cluster analysis to assess the spatial distribution of mixed milk feeding prevalence across Ethiopia’s administrative regions and cities. Empirical Bayesian Kriging was used for spatial interpolation to estimate mixed milk feeding prevalence in unsampled areas. The analysis utilized a maximum spatial cluster size threshold of 50% of the population to detect clusters of varying sizes. Ordinary least squares regression analysis identified significant spatial predictors. In geographically weighted regression analysis, the effect of predictor variables on the spatial variation of mixed milk feeding was detected using local coefficients. Results The overall weighted prevalence of Mixed Milk Feeding (MMF) in Ethiopia was 10.12% (95% CI: 7.8, 13.01). This prevalence shows significant regional variations across the country emphasizing regional disparities in prevalence and distribution. The Global Moran’s I statistic was 0.14, with a Z-score of 3.18 and a p-value of < 0.001, indicating a significant spatial clustering of MMF prevalence. Hotspots of mixed milk feeding were identified in Somali, Dire Dawa, and Afar, while cold spots were observed in Amhara, Tigray, Benishangul Gumuz, SNNPR, and parts of Oromia. Household wealth (middle wealth index) and lack of baby postnatal checkups emerged as key influencers of mixed milk feeding practices. Conclusion The study found significant regional variations in mixed milk feeding practices in Ethiopia. Households with middle wealth index and baby without postnatal check were significant spatial predictors of mixed milk feeding. To reduce mixed milk feeding prevalence, targeted interventions should engage community leaders, enhance breastfeeding education in maternal health services, and integrate counseling into routine healthcare to support informed maternal choices and improve child health outcomes nationwide.